2023
DOI: 10.1001/jamapediatrics.2023.3566
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostic Yield of Exome Sequencing and Chromosomal Microarray in Short Stature

Qing Li,
Zefu Chen,
Jie Wang
et al.

Abstract: ImportanceCurrently, the diagnostic yield of exome sequencing (ES) and chromosomal microarray analysis (CMA) for short stature cohorts is uncertain. Despite previous studies reporting the widespread use of ES and CMA, a definitive diagnostic yield has not been established.ObjectiveTo investigate the diagnostic yield of ES and CMA in short stature.Data SourcesA systematic literature search was conducted using relevant keywords in 3 databases (PubMed, Embase, and Web of Science) in February 2023.Study SelectionE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Our study demonstrated the high diagnostic yield (47.2%) in non-SGA SS patients compared to the general detection rate of 27.1% (95% CI, 18.1-37.2%), reported in a metaanalysis of 20 studies of patients with SS [52].…”
Section: Discussionsupporting
confidence: 46%
“…Our study demonstrated the high diagnostic yield (47.2%) in non-SGA SS patients compared to the general detection rate of 27.1% (95% CI, 18.1-37.2%), reported in a metaanalysis of 20 studies of patients with SS [52].…”
Section: Discussionsupporting
confidence: 46%
“…In this editorial commentary, I will analyze the recent paper authored by Li et al , delving into the dynamic role of contemporary technologies in deciphering the genetic intricacies associated with short stature ( 1 ). The exploration encompasses an in-depth assessment of their diagnostic performance, challenges encountered, and the significant potential they bear for advancing patient care.…”
Section: Understanding Short Staturementioning
confidence: 99%
“…Short stature, defined as a height that is less than 2 standard deviations (SDs) from the mean for the respective age and gender ( 1 , 2 ). The aetiology of short stature is multifactorial and can result from genetic factors, hormonal factors such as growth hormone, thyroid hormones, and cortisol, and a spectrum of environmental factors (prenatal and postnatal), or a combination of both.…”
Section: Understanding Short Staturementioning
confidence: 99%
See 1 more Smart Citation